The Financial Consumer Protection on Economic Financial Performance of Life Insurance: Evidence from Indonesia - Agus, Irma; Hadiprajitno, P. Basuki (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to analyze the effect of consumer protection implementation on financial performance of life insurance in Indonesia. It takes to explain the vital role of consumer protection in maintaining the financial performance of the life insurance industry by focusing on five key aspects of consumer protection: Data Confidentiality and Security, Financial Literacy, Service and Complaint Resolution, Information Submission (Product Marketing), and Standard Agreements. This research describes how effective implementation of these principles is to the improvement of financial performance. We find that there is a significant effect of consumer protection on financial performance. Data security, financial literacy and complaint resolution have a positive influence on financial performance. Moreover, the information delivery, and standard agreements aspects did not show a significant relationship in this context. By highlighting the crucial role of consumer protection in maintaining financial stability, the study offers valuable recommendations for regulators and life insurance practitioners to strengthen consumer protection policies and practices.